INFLUENCE OF LEADERSHIP QUALITY, MOTIVATION, COMMUNICATION, AND LOYALTY TO EMPLOYEE PERFORMANCE IN PT. SARI WARNA ASLI II - Bimo Hardianto; Kartika Hendra Titisari; Istiatin Istiatin (University of Islam Malang, 2021)
The purpose of this study is to determine the effect of leadership quality, motivation, communication, and loyalty on employee performance in the office department at PT Sari Warna Asli II. This research is quantitative research and the type of research used in this research is explanatory research. The data source used in this study is derived from primary data, namely questionnaires that are shared with employees of PT. Sari Warna Asli II Boyolali. The time used in this study is January 24 to February 6, 2021. The population in this study is the entirety of pt office department employees. Sari Warna Asli unit II, Boyolali. The population in this study was 81 employees and all were sampled. Data collection techniques in this study include, documentation, questionnaires, interviews, and library studies. Data analysis using multiple linear regressions, model feasibility tests, hypothesis tests, determination coefficient tests using SPSS.. The results showed that the variables of leadership quality, motivation, communication, had a positive and significant effect on the performance of employees in the office department of PT Sari Warna Asli II, but the loyalty variable had no effect on the performance of employees in the office department of PT Sari Warna Asli II. The coefficient of determination test or Adjusted R Square in this study is 75%.